2018
DOI: 10.3390/ijms19123936
|View full text |Cite
|
Sign up to set email alerts
|

Rice Overexpressing OsNUC1-S Reveals Differential Gene Expression Leading to Yield Loss Reduction after Salt Stress at the Booting Stage

Abstract: Rice nucleolin (OsNUC1), consisting of two isoforms, OsNUC1-L and OsNUC1-S, is a multifunctional protein involved in salt-stress tolerance. Here, OsNUC1-S’s function was investigated using transgenic rice lines overexpressing OsNUC1-S. Under non-stress conditions, the transgenic lines showed a lower yield, but higher net photosynthesis rates, stomatal conductance, and transpiration rates than wild type only in the second leaves, while in the flag leaves, these parameters were similar among the lines. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…These studies reported that heterosis in the hybrid is the result of allelic interactions between its parental genomes and subsequent altered programming of genes promoting growth, tolerance to stress, and fitness of hybrids [16]. However, the usage of flag leaf in our study makes our exceptional when compared other reports, as it is considered as the energy sources for rice grain development [17][18][19]. In order to deduce the complex molecular mechanism of rice heterosis, an in-depth understanding is required at the level of global gene expression in hybrids and the parents.…”
Section: Introductionmentioning
confidence: 67%
“…These studies reported that heterosis in the hybrid is the result of allelic interactions between its parental genomes and subsequent altered programming of genes promoting growth, tolerance to stress, and fitness of hybrids [16]. However, the usage of flag leaf in our study makes our exceptional when compared other reports, as it is considered as the energy sources for rice grain development [17][18][19]. In order to deduce the complex molecular mechanism of rice heterosis, an in-depth understanding is required at the level of global gene expression in hybrids and the parents.…”
Section: Introductionmentioning
confidence: 67%
“…There were two GSS events, for the combination of Intron 147728 and Intron 147745 in the gene, OsNUC1 ( LOC_Os04g52960 ), which has been identified as a salt‐responsive gene (Sripinyowanich et al ., 2013; Udomchalothorn et al ., 2017; Boonchai et al ., 2018). Introns 147728 and 147745, located in between the third and fourth exons of OsNUC1 , are a pair of AltA events with the same 5′ end and similar lengths (Table 2), but Intron 147728 is six nucleotides shorter than Intron 147745 at the 3′ end (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…OsNUC1 contains five domains: bipartite nuclear localisation signal (NLS), the SR region, two RNA recognition motifs (RRM), and a C‐terminal glycine‐ and arginine‐rich (GAR) domain (Sripinyowanich et al ., 2013). Previous studies have reported that OsNUC1 is a salt‐responsive gene and its over‐expression enhances salt tolerance in transgenic Arabidopsis and rice (Sripinyowanich et al ., 2013; Udomchalothorn et al ., 2017; Boonchai et al ., 2018). In our study, the transcript abundance of OsNUC1 was significantly downregulated under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…In total, there were 12 samples of RNA-seq data; six salinity stress samples and six control samples. Complete sample preparation and data analysis are explained in Boonchai et al (2018) [33] . Briefly, total RNA was extracted from rice flag leaf samples of both control and salt stress conditions by using Invitrogen’s Concert™ Plant RNA Reagent.…”
Section: Methodsmentioning
confidence: 99%